Ciudadanía, procesos de globalización y democracia - Judit Bokser (Revista Enfoques, 2006)
The present work proposes an analysis of the development of the concept of citizenship from a philosophical and politological approach. In order to do this, the author situates herself within the process of globalization and its implications for the democratic consolidation and the challenges that this new scene implies. From this perspective, citizenship is seen as a line of debate subject to constant construction due to the transformations that other theoretical and institutional devices -like the Nation-State and democratic regimes- are undergoing, developing an interesting perspective about the relationship established between the communitarianism, liberalism and republicanism and its articulations with the cultural, institutional, and political dimensions.